ANALISIS PENGARUH PEMBATASAN SOSIAL BERSKALA BESAR TERHADAP RESPON PASAR MODAL DILIHAT DARI HARGA SAHAM SEKTOR PROPERTI DAN REAL ESTATE YANG ADA DI BEI TAHUN 2020-2021 - Respati, Laras Laksita; Fitanto, Bahtiar (Contemporary Studies in Economic, Finance and Banking, 2022)
This study aims to analyze the reaction of the capital market to before and after the implementation of the PSBB policy seen from the value of the abnormal return, stock return and trading volume activity variables. This research is a quantitative research, with property and real estate on the Stock Exchange as the population and takes 60 companies as samples with purposive sampling technique. The results of this study indicate that the three variables are significantly affected by the announcement of the implementation of the PSBB policy by showing a decrease in the value of the variable after the policy is implemente.